Patai's Chemistry of Functional Groups 2009
DOI: 10.1002/9780470682531.pat0314
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Oxiranes with Organolithium Reagents

Abstract: General Introduction α‐/β‐Deprotonation β‐Deprotonation Oxirane Ring Opening by Organolithium Reagents Synthesis and Reactivity of Lithiooxiranes General Conclusion Acknowledgments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 312 publications
0
2
0
Order By: Relevance
“…The ring strain in oxiranes makes them useful reagents for a wide variety of synthetic pathways under mild conditions. Their rich chemistry in the presence of organolithium reagents has been discussed in several excellent reviews. Although the possibility of competition between α-lithiation and β-elimination in oxirane chemistry has been well-recognized, further evolution of the intermediates produced by these initial steps along the two pathways remain to be studied and motivates the present work.…”
Section: Introductionmentioning
confidence: 99%
“…The ring strain in oxiranes makes them useful reagents for a wide variety of synthetic pathways under mild conditions. Their rich chemistry in the presence of organolithium reagents has been discussed in several excellent reviews. Although the possibility of competition between α-lithiation and β-elimination in oxirane chemistry has been well-recognized, further evolution of the intermediates produced by these initial steps along the two pathways remain to be studied and motivates the present work.…”
Section: Introductionmentioning
confidence: 99%
“…However, the nucleophilicity of the phosphazenyl-stabilized anion seems to be too low to achieve ring opening of the oxirane leading to intermediate species Li-IIa . 36 After some experimentation (including various temperatures, activation by CeCl 3 , etc. ), we found that performing the addition of the electrophile at –35 °C and then heating the reaction mixture at 45 °C for 2 h gave, after aqueous workup, the expected spiro-1,2-oxaphospholanone 17a isolated in a yield of 86% by precipitation from diethyl ether.…”
mentioning
confidence: 99%